Pengaruh Pemberian Fermentasi Bungkil Biji Kedelai (Glycine Max L. Merri) pada Pakan Ikan Terhadap Pertumbuhan Ikan Nila (Oreochromis Niloticus) - Wulandari, Evi Sri; Marjanah, Marjanah; Mawardi, Mawardi (Multiverse: Open Multidisciplinary Journal, 2023)
This study investigates the impact of fermented soybean meal and different soybean compositions on the growth of tilapia (Oreochromis niloticus), a freshwater fish. The experimental method consisted of five treatments and five replications. The ANOVA test revealed a significant effect of fermented soybean meal on tilapia growth (Fcount > Ftable, 109.6316 > 2.87, p < 0.01). The highest final body weight observed was 18.4 grams, while the lowest was 10.4 grams. Treatment P4, which involved 80% soybean meal, exhibited the highest fish growth. Conversely, the control treatment (P0) without soybean meal resulted in limited nila growth. These findings demonstrate that the provision of soybean meal has a substantial influence on the growth of tilapia.